THE ROLE OF OUR NATIONAL CULTURE IN THE DEVELOPMENT OF HISTORICAL REFORMS - Dilmurod Rashitovich Shaikhov (Galaxy International Interdisciplinary Research Journal, 2022)
In the article, it should be important to understand the place of our national culture in the development of historical reforms and to what extent the competence of national-cultural values. It has been analyzed that our country has developed its national values and culture at a higher level, and created a unique new history of the new Uzbekistan, as it continues to strengthen its place and position in the world arena.